Assessment of vitamin D status in Czech children - Sochorová, Lenka; Hanzlíková, Lenka; Černá, Milena; Vosátková, Michala; Grafnetterová, Anna Pinkr; Fialová, Alena; Kubínová, Růžena (Central European journal of public health, 2018)
OBJECTIVE: Vitamin D deficiency is a global health problem. The aim of this study was to determine the proportion of Czech children with vitamin D deficiency and examine related factors. METHODS: The study subjects were 419 healthy children aged 5 and 9 years. Severe vitamin D deficiency was defined as a serum 25(OH)D level of < 25 nmol/L (3% of children), deficiency as that of 25-50 nmol/L (24% of children), insufficiency as that of 50-75 nmol/L (40% of children) and sufficiency as that of > 75 nmol/L (34% of children). RESULTS: Serum 25(OH)D levels varied mainly with season. The highest levels of 25(OH)D were reached in autumn (median: 79.0 nmol/L), followed by summer (median: 67.8 nmol/L) and winter (median: 56.0 nmol/L). The lowest median value (49.8 nmol/L) was detected in spring. CONCLUSION: Children with sufficiency 25(OH)D levels were more frequently exposed to the sun and exposed a larger part of their body to the sun while spending time outdoors. Levels of 25(OH)D were also associated with using vitamin D supplements within six weeks before sampling.
Keywords: Child, Preschool; Risk Factors; Vitamin D Deficiency; Česká republika; Child; 25(OH)D levels; dítě; vitamin D; Czech Republic; předškolní dítě; lidé; roční období; Seasons; Humans; rizikové faktory; human biomonitoring; Vitamin D; nedostatek vitaminu D; children